ESTIMATING THE IMPACT OF STERILIZATION ON THE CANINE POPULATION GROWTH INDEX - Zumpano, Romina (2011)
The importance of dog population control relies on its implications in the transmission of zoonotic diseases, environmental pollution and possible injuries or attacks to humans. The aim of this work was to assess the impact of surgical neutering on the dog population in the city of Buenos Aires and Gran Buenos Aires area, Argentine through demographic rate indexes and tenancy behaviors. Data was obtained in a survey conducted in 2008 and 2009 in 136 households in the areas of Villa del Parque (CABA) and 143 of Villa Ballester (MGSM). A probabilistic model to calculate the annual growth rate of the dog population was developed. No differences were observed in the proportion of households keeping animals and those keeping dogs. However, MGSM presented an average rate of dogs per household higher than CABA. Population control indicators for surgical neutering were significantly higher whilst the average age of neutering was significantly lower in MGSM (p<0.01). No significant differences were observed in the growth rate estimation. The results suggest that with a female neutering level near 13%, the CABA canine population would grow an annual average of 13%, while considering a neutering level near 45% the MGSM dog population would grow an annual average of 8%. It is suggested that the growth of dog populations is linked to decisions and behaviors of the human population.